Mutation spectrum of chinese amyotrophic lateral sclerosis patients with frontotemporal dementia - Xunzhe Yang; Xiaohai Sun; Qing Liu; Liyang Liu; Jinyue Li; Zhengyi Cai; Kang Zhang; Shuangwu Liu; Di He; Dongchao Shen; Mingsheng Liu; Liying Cui; et al. (Orphanet Journal of Rare Diseases, 2022)
Abstract Background Studies have reported that a noncoding hexanucleotide repeat in C9ORF72, is the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) among Caucasian population, nevertheless it is rare in Chinese population. Therefore, we aimed to investigate the mutation spectrum of Chinese ALS patients with FTD (ALS-FTD). Methods ALS patients with and without cognitive impairments were enrolled. Clinical features were collected including age, sex, disease duration, ALSFRS-r, family history and cognitive evaluation. Thirty-six ALS genes were screened by whole exome sequencing (WES) and repeat-primed polymerase chain reaction (PCR) were used for detection of and abnormal repeat expansions of C9ORF72. Results A total of 1208 patients, including 66 familial ALS (FALS) and 1142 sporadic ALS (SALS) patients were included. Twenty-three patients with sporadic ALS and one familial ALS index had concomitant FTD, which accounts for 1.99% (24/1208) of patients with ALS. In sporadic ALS-FTD, one case harboring C9ORF72 expansion variant, two cases harboring ANXA11 variants and one individual carrying CCNF variant were identified. A recurrent UBQLN2 variant was detected in a familial ALS-FTD patient. All of the ALS-FTD patients carrying variants in known causative genes manifested motor symptom onset (two bulbar onset and three limb onset) and developed cognitive impairment thereafter. It is not easy to draw a conclusion of the genotype-phenotype association in ALS-FTD with certain variants, limited by the small number of patients. Conclusion Our findings provide an overview of spectrum of genetic variants in Chinese ALS-FTD patients. Variants of uncertain significance in UBQLN2, ANXA11 and CCNF were identified and further studies are required for causal relations of these variants with ALS-FTD.